Efeito da solução de hipoclorito de sódio em pH alto e sua interação com clorexidina nas propriedades viscoelásticas de um biofilme experimental - Pillar, Rafael (2017)
The present thesis consists of two articles that evaluated the influence of irrigation solutions on the viscoelastic properties of a double-species biofilm. The first study investigated the NaOCl 3% at alkaline pH stabilized by alkali or buffer on viscoelastic characteristics of an experimental biofilm (CDFF). Bacterial strains of S. oralis J22 and A. naeslundii T14v-J1 were grown on agar plates and introduced into the CDFF system where the biofilm was cultured for 96h at 37°C under continuous supply of modified BHI broth. The system was equipped with 15 samples-holder containing 05 hydroxyapatite (HA) discs, with a recess of 250 μm. HA discs were precoated for 14h at 4°C with an adhesion buffer prepared from lyophilized human saliva (1.5 g/l). The samples were divided into 05 groups (n = 05): Control Group - no treatment; NaOH group - 1: 1 ratio of 2 mol/l NaOH with Milli-Q water; 3% NaOCl standard group; 3% NaOCl stabilized group – (1:1) of 6% NaOCl with 2 mol/l NaOH and 3% NaOCl buffered group – (1:1) of 6% NaOCl with disodium phosphate buffer (Na2HPO4). A total of 20 μl were applied for 02 times: 60s and 300s. The samples were submitted to the low load compression testing (LLCT) with 20% and 50% deformations applied in 01s. The stress relaxation (%) and the elements: E1 (fast element: time interval t1 = 0.01s to 0.5s), E2 (intermediate: t2 = 0.5s to 3s) and E3 (slow: t3 = 3s to 100s) were monitored for 100s. The samples were submitted to optical coherence tomography (OCT) analysis, where the biofilm thickness was measured before and after treatment. The data were submitted to ANOVA. No statistical difference was observed in the stress relaxation values between the groups. There was also no statistically difference between the elements and the biofilm thickness before and after treatment, regardless of the time exposed (P > .05). We concluded that NaOCl solutions with a higher alkaline capacity were not able to alter the biofilm viscoelastic properties. The second study evaluated the interaction between 3% NaOCl and 2% chlorhexidine (CHX) on the viscoelastic properties described above. The same experimental biofilm was used, differing in the experimental groups as follows (n = 05): 3% NaOCl group (control 1); 2% CHX group (control 2); 2% CHX + 3% NaOCl group and 3% NaOCl + 2% CHX group. In the combining groups, a neutralizing solution was used between each exchange. 20 μl was applied. A time of 60s was evaluated. The samples were analyzed by LLCT and OCT with the same variables being evaluated (stress relaxation, elements, biofilm thickness). No statistical difference was found between the groups (P >.05). The combined use of NaOCl with CHX was not able to effectively alter the structure of the biofilm. Considering the results presented, it is possible to argue that either the isolated use of NaOCl, even with stable alkaline pH, or its combination with CHX, was not able to modify the viscoelastic characteristics of a dual-species biofilm.